2001
DOI: 10.1161/01.hyp.37.2.472
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationships for the Hypertensinogenic Activity of Ouabain

Abstract: Abstract-Elevated levels of an endogenous ouabain circulate in many patients with essential hypertension. However, in contrast to ouabain, digoxin does not induce hypertension. This study investigated the hypothesis that within a single cardiac glycoside, the structural elements that induce hypertension differ from those responsible for high potency as a sodium pump inhibitor. Normal male Sprague-Dawley rats received infusions of vehicle (VEH), rhamnose (RHA), ouabain (OUA), ouabagenin (OGN), dihydro-ouabain (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 26 publications
1
48
0
Order By: Relevance
“…Elevated EO levels were also observed in rodents with DOCA-salt hypertension (41,43), ACTH-hypertension (20, 20a, 115), reduced renal mass hypertension (108), and in salt-sensitive Milan strain rats on a high-salt diet (22,23). Indeed, a critical corollary to these reports is the evidence that prolonged administration of ouabain, itself (a Strophanthus steroid), but not digoxin or digitoxin (Digitalis steroids), elevates BP in normal rats and mice (19,60,72,74,75,116).…”
Section: Endogenous Ouabain and Other Endogenous Cardiotonic Steroidsmentioning
confidence: 97%
“…Elevated EO levels were also observed in rodents with DOCA-salt hypertension (41,43), ACTH-hypertension (20, 20a, 115), reduced renal mass hypertension (108), and in salt-sensitive Milan strain rats on a high-salt diet (22,23). Indeed, a critical corollary to these reports is the evidence that prolonged administration of ouabain, itself (a Strophanthus steroid), but not digoxin or digitoxin (Digitalis steroids), elevates BP in normal rats and mice (19,60,72,74,75,116).…”
Section: Endogenous Ouabain and Other Endogenous Cardiotonic Steroidsmentioning
confidence: 97%
“…nitric oxide; endothelial-dependent hyperpolarizing factor; phenylephrine THE PLASMA LEVELS of an endogenous circulating Na ϩ -K ϩ -ATPase inhibitor, characterized as ouabain or a closely related compound (17,36), are increased in several animal models of hypertension (19,39), as well as in human essential hypertension (20). Several studies have shown that chronic administration of ouabain induces hypertension, an effect that seems to be linked to the inhibition of the Na ϩ -K ϩ -ATPase (10,22,23,45,54), although sodium pump inhibition seems not to be the exclusive mechanism of the ouabain-hypertensive effect (26,31,32,52). This enzyme is found in most eukaryotic cells and is the main system involved in the maintenance of sodium homeostasis and the membrane potential, essential factors for controlling vascular tone and blood pressure.…”
mentioning
confidence: 99%
“…, although sodium pump inhibition seems not to be the exclusive mechanism of the ouabain-hypertensive effect (26,31,32,52). This enzyme is found in most eukaryotic cells and is the main system involved in the maintenance of sodium homeostasis and the membrane potential, essential factors for controlling vascular tone and blood pressure.…”
mentioning
confidence: 99%
“…Ouabain and a series of structurally related analogs have hypertensinogenic activity, regardless of their potency as Na + pump inhibitors (32). In addition, Ward et al (33) suggested that adrenocortical cells express ouabain receptors that are distinct from the Na + pumps.…”
Section: Acute Effects Of Picomole Quantities Of Ouabain On Vascular mentioning
confidence: 99%